Ultrasound evaluation of gallbladder wall thickness for predicting severe dengue: a systematic review and meta‑analysis - Shahsavand Davoudi, Amirhossein; Harandi, Hamid; Samiee, Reza; Forghani, Shayan; Mohammadi, Keyhan; Shafaati, Maryam (The Ultrasound Journal, 2025)
Background: The prevalence of dengue fever (DF), a mosquito-borne viral disease, is rising worldwide. Its severe manifestations like thrombocytopenia and plasma leakage are associated with increased mortality. Ultrasound-detected gallbladder wall thickening (GBWT) has been suggested as a potential indicator of the severity of the disease.Aims: This systematic review and meta-analysis evaluated the predictive value of GBWT in identifying patients at risk for severe dengue.Methods: Following the PRISMA 2020 guidelines, we conducted a systematic search of Web of Science, PubMed, Embase, and Scopus. Among the inclusion criteria were original studies that assessed GBWT across various dengue severity categories. Then, we performed a meta-analysis using a random effects model and subgroup analyses based on severity criteria to determine the relationship between GBWT and severe dengue.Results: For the meta-analysis, 19 studies qualified for the inclusion criteria. There was a significant association between GBWT and severe dengue, according to the odds ratio (OR) of 2.35 (95% CI 1.88–2.82, p